2014
DOI: 10.1073/pnas.1412752111
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenBatrachochytrium dendrobatidisdisturbs the frog skin microbiome during a natural epidemic and experimental infection

Abstract: Significance Animals are inhabited by communities of microbes (the microbiome) that potentially interact with pathogens. Detailed studies of microbiome–pathogen interactions in nature are rare, and even when correlations are observed, determining causal relationships is challenging. The microbiome–pathogen relationship is of particular interest in the case of Batrachochytrium dendrobatidis , a chytrid fungus that infects the skin of amphibians and is causing amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
294
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(316 citation statements)
references
References 77 publications
(103 reference statements)
11
294
7
Order By: Relevance
“…This suggests that A. zeteki microbial communities are at least somewhat resistant and/or resilient to invasion. This is contrary to a recent study that found the cutaneous bacterial community structure of Rana sierrae was affected by the presence of Bd and its density on the frog [57].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This suggests that A. zeteki microbial communities are at least somewhat resistant and/or resilient to invasion. This is contrary to a recent study that found the cutaneous bacterial community structure of Rana sierrae was affected by the presence of Bd and its density on the frog [57].…”
Section: Discussioncontrasting
confidence: 99%
“…These OTUs may have facilitated the colonization and growth of Bd or may have been opportunistic pathogens. In addition, the relative abundance of these OTUs may have increased because Bd was able to negatively affect the abundance of other OTUs [57]. Facilitation of Bd growth and colonization could occur either when symbiotic bacteria shift their metabolite profiles in a way that favours Bd [35] or by reducing the capability of other microbes to inhibit Bd.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of amphibian skin microbiomes is rapidly increasing (Jani and Briggs, 2014;Kueneman et al, 2014;Walke et al, 2014). Exploring skin bacterial communities across different amphibian developmental stages and the defensive functions those microbes play, particularly prior to the development of the adaptive immune function, is an important and understudied area.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods for investigating microeukaryotes are just emerging, allowing us to further consider the role of nonbacterial microbes on the skin. In addition, there are few next-generation microbial data sets that compare Bd-positive and Bd-negative sites (Jani and Briggs, 2014). Within this study we begin to fill these knowledge gaps including describing A. boreas skin communities across developmental stages from Bd-positive and -negative sites across the host range in Colorado; surveying microeukaryotes from amphibians utilizing high throughput sequencing; and providing the first application of a cultureindependent database of known and expected Bd-inhibitory isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In Rana sierrae, a high elevation species that has experienced significant Bd-driven declines in North America, Bd infection resulted in the disturbance of skin bacterial communities in both wild and captive amphibians (Jani & Briggs 2014). However, in populations in which Bd had become enzootic, skin bacterial populations appeared to remain relatively stable with changes in Bd infection intensity, although the sample size was too small to make conclusions (Jani & Briggs 2014). Skin bacterial community diversity has also been found to be lower in populations of a susceptible Panamanian frog species where Bd has become endemic (Rebollar et al 2016).…”
Section: How Does Sloughing Interact With Bd and The Frog Skin Microbmentioning
confidence: 99%